2020
DOI: 10.18632/aging.103084
|View full text |Cite
|
Sign up to set email alerts
|

Activated CD4+ T cells-derived exosomal miR-142-3p boosts post-ischemic ventricular remodeling by activating myofibroblast

Abstract: Cardiac fibrosis is a primary phenotype of cardiac remodeling that contributes to cardiac dysfunction and heart failure. The expansion and activation of CD4 + T cells in the heart has been identified to facilitate pathological cardiac remodeling and dysfunction; however, the underlying mechanisms remained not well clarified. Herein, we found that exosomes derived from activated CD4 + T cells (CD4-activated Exos) evoked pro-fibrotic effects of cardiac fibroblasts, and their delivery into the heart aggravated ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…But the experiments of Cai et al demonstrated that miR-142-3p enriched in exosomes derived from activated CD4 + T cells (CD4-activated Exos) targeted and inhibited the expression of Adenomatous Polyposis Coli, contributing to the activation of WNT signaling pathway and activation of cardiac fibroblast, thus evoking pro-fibrotic effects of cardiac fibroblasts. And the delivery of CD4-activated Exos into the heart aggravated cardiac fibrosis and caused post-MI dysfunction 52 . Therefore, the cardioprotective effects of exosomes secreted from DCs deserve further research.…”
Section: Immune Cell-derived Exosomes In Immunomodulation After Amimentioning
confidence: 99%
“…But the experiments of Cai et al demonstrated that miR-142-3p enriched in exosomes derived from activated CD4 + T cells (CD4-activated Exos) targeted and inhibited the expression of Adenomatous Polyposis Coli, contributing to the activation of WNT signaling pathway and activation of cardiac fibroblast, thus evoking pro-fibrotic effects of cardiac fibroblasts. And the delivery of CD4-activated Exos into the heart aggravated cardiac fibrosis and caused post-MI dysfunction 52 . Therefore, the cardioprotective effects of exosomes secreted from DCs deserve further research.…”
Section: Immune Cell-derived Exosomes In Immunomodulation After Amimentioning
confidence: 99%
“…Infiltrating CD4+ T cells are important drivers of inflammation and fibrosis after MI [ 178 ] and exosomes from activated CD4+ T cells promoted cardiac fibroblast activation in vitro and exacerbated fibrosis and heart dysfunction in mouse MI [ 179 ]. This effect was attributed to exosomal 142-3p, which promoted Wnt signaling and cardiac fibroblast activation by attenuating expression of the Wnt suppressor molecule, adenomatous polyposis coli [ 179 ].…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…To sum up, T-activated EXs are the critical signal carriers in cardiac fibrosis following MI, and exosomal miR-142-3p serves as the signal conductor, providing a potential therapeutic target for treating MI-related cardiac fibrosis. 116 In conclusion, systemic deliveries of helpful exosomes or specific targeting of detrimental exosomes can provide an effective therapeutic window for treating MI-injured myocardium. However, further experimental studies are necessary to understand the exact effects of these exosomes as well as other immune cells, like neutrophils, mast cells and B lymphocytes, in the infracted myocardium after MI.…”
Section: Exosomes Secreted From Activated Cd4 + T Cells (T-activated Exs)mentioning
confidence: 94%